Relations Between Cash Flows Risaralda Companies and Regional Gross Domestic Product for Commercial Sector in the Period 2002-2011 - Rincón, Felipe
In this article the cash flows of the companies of Risaralda and the regional gross domestic product for the commercial sector are analyzed. Its aim is to establish the relationship to companies that reported financial statements to the Superintendency of Companies for the period 2002-2011 and the regional Gross Domestic Product (GDP).The research was documentary, descriptive-correlational nature, because throughout the process flows of cash from operations, financing and investment to subsequently identify, establish correlations with the different macroeconomic variables such as unemployment, interest rates, the DTF and the IGBC. These relationships, identify year by year increases or decreases in cash flows and its impact on the economy for the same periods.